Association between multimeric adiponectin and free leptin index with atherogenic dyslipidemia in non-diabetic obese men (Medical Journal of Indonesia, 2011)
Background: To analyze the role of various adiponectin and free leptin index on the occurrence of atherogenic dislipidemia in non-diabetic central obese men.Methods: This is a cross-sectional study on 120 non-diabetic central obese men that was done in Jakarta. The measured indicators were total adiponectin, high molecular weight adiponectin (HMW adiponectin), medium molecular weight adiponectin (MMW adiponectin), low molecular weight adiponectin (LMW adiponectin), leptin, soluble leptin receptor, triglycerides, high-density lipoprotein cholesterol (HDL cholesterol), low density lipoprotein cholesterol (LDL cholesterol) and apolipoprotein B (Apo B). Atherogenic dyslipidemia was characterized by reduced level of HDL cholesterol, and high levels of triglyceride and small dense LDL (sdLDL). Ratio of LDL cholesterol and Apo B were calculated to get sdLDL. Free Leptin Index (FLI) was the ratio between total leptin and soluble leptin receptor (sOB-R), and median values were used as cut off to defi ne high and low values of each parameter. Cross tabulation were done on categorical data. Relationships between multimeric adiponectin and free leptin index with atherogenic lipids were analyzed by using Spearman analysis. Further, the interaction of all indicators with the occurence of atherogenic dyslipidemia was analyzed using binary logistic regression.Results: A negative correlation of HMW adiponectin with atherogenic dyslipidemia (p < 0.05), whereas there were no correlation between MMW adiponectin and LMW adiponectin with atherogenic dyslipidemia (p > 0.05). Free Leptin Index was associated positively with atherogenic dyslipidemia (p < 0.05). Odds Ratio (OR) of HMW adiponectin for the occurrence of atherogenic dyslipidemia was 3.62 (p < 0.05), where as OR of FLI with atherogenic dyslipidemia was 4.57 (p < 0.05).Conclusion: HMW Adiponectin and FLI might contribute to atherogenic dyslipidemia in central obese non-diabetic males. (Med J Indones 2011; 20:119-24)Keywords: HMW adiponectin, LMW adiponectin, MMW adiponectin, total adiponectin